NRMNet: Building a National Resource for Mentorship, Networking and Professional Development to Enhance Diversity - Javier, Damaris (Ethn Dis, 2021)
BACKGROUND: To address the need for diversifying the biomedical research workforce, the National Institutes of Health (NIH) established the Diversity Program Consortium (DPC) with the goal of developing, implementing, assessing, and disseminating interventions and programs to enhance the participation and persistence of individuals from underrepresented backgrounds in biomedical research careers. INTERVENTION: As part of the DPC initiative, the NIH funded the National Research Mentoring Network (NRMN), which aimed to increase diversity of the biomedical research workforce through culturally responsive mentorship, networking, and professional development. In 2015, the NRMNet portal was developed to provide a broad-based network of mentors who are accessible to diverse mentees across the country. The portal also provides networking and professional development resources that support mentee transitions from one career stage to the next. RESULTS: NRMNet is the gateway for career stage-specific mentorship, networking, resources, and professional development programs for trainees across the biomedical, behavioral, clinical, and social sciences. In the first five years, the NRMN strategic recruitment efforts resulted in an expanded network of nearly 13,000 diverse mentors and mentees with NRMN representation in all 50 states and Puerto Rico. Consistently, over the first five years, racial and ethnic diversity was reflected in composition of mentee and mentor groups: 66% of 6,526 mentees and 33% of 3,866 mentors were from underrepresented groups. CONCLUSIONS: The NRMNet portal is a promising effort for enhancing participation and continued engagement of undrerepresented individuals in biomedical research careers by providing culturally responsive mentorship, networking, and professional development for individuals at all career stages.